The Religiosity and Quality of Life: A Meta-Analytic Synthesis of Global Evidence (2015–2024) - Arrosyid, Muhammad Salman; Marzuki, Marzuki; Widihastuti, Widihastuti; Santos, Mariano Dos (Religious: Jurnal Studi Agama-Agama dan Lintas Budaya, 2025)
This study aims to examine the relationship between religiosity and quality of life through a comprehensive meta-analysis, motivated by inconsistent findings in previous research that range from strong positive correlations to weak or non-significant associations. Understanding this relationship is crucial for clarifying the psychological and social functions of religiosity in contemporary societies. This research employed a quantitative meta-analytic design by synthesizing 31 Scopus-indexed empirical studies published between 2015 and 2024. Data were extracted in the form of correlation coefficients and analyzed using a random-effects model, accompanied by heterogeneity tests, publication bias assessments, and robustness checks. This methodological approach ensured systematic data integration without presenting technical details excessively. The findings show a significant positive correlation between religiosity and quality of life (r = 0.32; 95% CI [0.20, 0.44]; p < 0.001). Substantial heterogeneity (Q = 656.535; p < 0.001) suggests that cultural, demographic, and methodological differences may moderate this relationship. The absence of publication bias and a high fail-safe N value (5,109) further confirm the stability of the results. These findings imply that religiosity functions as a meaningful psychological, social, and spiritual resource capable of enhancing individual well-being across diverse populations. The results contribute to the development of resilience- and spirituality-based interventions in psychological, health, and community settings. The originality of this study lies in its synthesis of a full decade of empirical evidence, offering the most updated meta-analytic confirmation of the religiosity–quality of life relationship. This research provides new value by integrating large-scale data, addressing inconsistencies in prior findings, and strengthening theoretical and practical understanding of how religiosity contributes to human well-being.